Description of novel resistance islands harbouring blaCTX-M-2 in IncC type 2 plasmids. (September 2021) - Papa-Ezdra, R.; Cordeiro, N.F.; Di Pilato, V.; Chiarelli, A.; Pallecchi, L.; Garcia-Fulgueiras, V.; Vignoli, R.
Highlights: bla CTX-M-2 was located in a complex class 1 integron In 35 ::IS CR1 :: bla CTX-M-2 . In 35 was inserted in two novel transposons (Tn 7057 and Tn 7058 ). Both transposons are a hybrid of Tn 1696, Tn 21 and Tn 1000 /Tn 2* . Tn 7057 and Tn 7058 were located in IncC type 2 plasmids belonging to ST3. The conjugation frequency was in the order of 10 –3 for both plasmids. ABSTRACT: Objectives: We sequenced two IncA/C plasmids harbouring bla CTX-M-2 in Klebsiella pneumoniae clinical isolates and compared their antibiotic resistance islands. Methods: Transconjugants were obtained from two clinical K. pneumoniae isolates harbouring bla CTX-M-2 . Plasmid DNA from transconjugants underwent short-read whole-genome sequencing, reads were assembled, and gaps were closed by PCR and sequencing. Determination of plasmid replicons, antibiotic resistance genes, identification and characterisation of insertion sequence (IS) elements, and comparison with publicly available plasmid sequences were performed. Results: bla CTX-M-2 was located in a complex class 1 integron In 35 ::IS CR1 :: bla CTX-M-2, inserted in two different transposons designated Tn 7057 and Tn 7058, that reside in the resistance islands of plasmids pUR-KP0923 and pUR-KP1025, respectively. The general modules of both transposons were In 35 ::IS CR1 :: bla CTX-M-2 –Tn 1000- like–Tn 2* –IS Kpn11 - 12 - 13 variable module–ΔTn 21 . In Tn 7057 there was ΔIS 10R – catA2 associated with an additional IS Kpn13 . Both plasmids belonged to IncC type 2 and ST3. pUR-KP0923 was 167 138 bp in length and had a 37 926-bp resistance island at position 4 (RI-4). Plasmid pUR-KP1025 was 168 128 bp with a RI-4 of 36 222 bp. Conclusion: This report describes the molecular nature of two transposons (Tn 7057 and Tn 7058 ) harbouring bla CTX-M-2 that reside in IncC type 2 ST3 plasmids. These transposons mediate resistance to oxyimino-cephalosporins, gentamicin and, in the case of Tn 7057, chloramphenicol. CTX-M-2 is an important extended-spectrum β-lactamase (ESBL) to South American epidemiology. It is remarkable that despite being only two plasmid sequences, the information revealed here could contribute to a better understanding of the resistance islands from IncC type 2 plasmids.